Dynamic Stability of Moderately Thick Composite Laminated Skew Plates using Finite Strip Method - Jamshid Fazilati (Mechanics of Advanced Composite Structures)
The dynamic instability regions of composite laminated skew flat plates subjected to uniform in-plane axial end-loading are investigated. The in-plane loading is assumed as a combination of a time-invariant component and a harmonic time-varying component uniformly distributed along two opposite panel ends’ width. In case of some loading frequency-amplitude pair-conditions, the model is subjected to instabilities. The dynamic instability margins of the skewed flat panel have been extracted using a developed semi-analytical finite strip formulation. The method has been developed based on a full-energy approach through the principle of the virtual work. The effects of thickness have been included by utilizing a third-order Reddy type shear deformation theory. The effects of boundary conditions as well as geometry on the instability load-frequency regions are derived using the Bolotin's first-order approximation. In order to demonstrate the capabilities of the developed method in predicting the structural dynamic behavior, some representative results are obtained and compared with those in the literature wherever available.